(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Even though the idea of arranging development in rural regions has undergone constant evolution, rural development is still an old topic. Due to the overwhelming importance of rural components in these nations’ economy, rural development has taken precedence in less developed nations. Like economic development, rural development shows a desire to lessen exploitation, inequality, and poverty. Since the majority of socioeconomic indicators, such as income, nutrition, life expectancy, physical infrastructure, literacy, and the provision of social services in the rural areas, compare unfavourably with those in the urban areas, this may also be interpreted as a concern for "urban biases" in development in the majority of countries. Rural development refers to the desired qualitative and quantitative transformation of rural areas. It can also be said that Rural development is the process of reducing hunger, poverty, unemployment, and inequality, which ultimately raises the standard of living for the majority of rural residents.